How Will Climate Change Shift Agro-Ecological Zones and Impact African Agriculture? - Kurukulasuriya, Pradeep; Mendelsohn, Robert (World Bank, Washington, DC, 2012)
The study develops a new method to measure the impacts of climate change on agriculture called the Agro-Ecological Zone (AEZ) Model. A multinomial logit is estimated to predict the probability of each AEZ in each district. The average percentage of cropland and average crop net revenue are calculated for each AEZ. Then an estimate of the amount of cropland in Africa and where it is located is provided. Using current conditions, the model calculates baseline values of cropland and crop net revenue, and estimates the future impact of climate change using two scenarios-harsh and mild. Total cropland does not change much across the two climate scenarios. However, the predicted change in African crop revenue ranges from a loss of 14 percent in the mild climate scenario to 30 percent in the harsher climate scenario. The analysis reveals that the greatest harm from climate change is that it will shift farms from high to low productive AEZs. The approach not only identifies the aggregate impacts, but also indicates where the impacts occur across Africa. The central region of Africa is hurt the most, especially in the harsher climate scenario. The Agro-Ecological Zone Model is a promising new method for valuing the long-term impacts of climate change on agriculture.